2017
DOI: 10.1371/journal.pone.0178291
|View full text |Cite
|
Sign up to set email alerts
|

Association of ATG16L1 gene haplotype with inflammatory bowel disease in Indians

Abstract: Inflammatory bowel disease (IBD) is characterized by multigenic inheritance. Defects in autophagy related genes are considered to show genetic heterogeneity between populations. We evaluated the association of several single nucleotide polymorphisms (SNPs) in the autophagy related 16 like 1 (ATG16L1) gene with IBD in Indians. The ATG16L1 gene was genotyped for ten different SNPs using DNA extracted from peripheral blood of 234 patients with Crohn’s disease (CD), 249 patients with ulcerative colitis (UC) and 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Studies have shown that some of the effective genes in autophagy, including ATG16L1 and IRGM, are associated with IBD, especially Crohn's disease (Kabat et al, 2016;X. C. Lu et al, 2013;Moon et al, 2012;Nguyen et al, 2014;Nunes et al, 2014;Pugazhendhi, Baskaran, Santhanam, & Ramakrishna, 2017). ATG16L1, as an adaptor protein, is constitute an ATG5-binding region and coiled-coil domain (CCD; for self-dimerization), in N-and amino terminal, respectively (Mizushima et al, 2003).…”
Section: Mirnas and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that some of the effective genes in autophagy, including ATG16L1 and IRGM, are associated with IBD, especially Crohn's disease (Kabat et al, 2016;X. C. Lu et al, 2013;Moon et al, 2012;Nguyen et al, 2014;Nunes et al, 2014;Pugazhendhi, Baskaran, Santhanam, & Ramakrishna, 2017). ATG16L1, as an adaptor protein, is constitute an ATG5-binding region and coiled-coil domain (CCD; for self-dimerization), in N-and amino terminal, respectively (Mizushima et al, 2003).…”
Section: Mirnas and Autophagymentioning
confidence: 99%
“…Autophagy is a process that greatly helps in saving cellular energy by eliminating unnecessary components; this condition is more important in certain conditions, such as those in which food shortages exist or while dealing with pathogens (Nunes et al, ). Studies have shown that some of the effective genes in autophagy, including ATG16L1 and IRGM, are associated with IBD, especially Crohn's disease (Kabat et al, ; X. C. Lu et al, ; Moon et al, ; Nguyen et al, ; Nunes et al, ; Pugazhendhi, Baskaran, Santhanam, & Ramakrishna, ). ATG16L1, as an adaptor protein, is constitute an ATG5‐binding region and coiled‐coil domain (CCD; for self‐dimerization), in N‐ and amino terminal, respectively (Mizushima et al, ).…”
Section: Role Of Mirnas In Ibd Pathogenesismentioning
confidence: 99%
“… 26 In addition, ATG16L1 rs2241880 polymorphism is associated with rheumatoid arthritis in China. 27 Pugazhendhi 21 confirmed that the allele and genotype frequencies of the ATG16L1 mutant rs4663402 are associated with Crohn's disease and ulcerative colitis in India. Similarly, Glas et al 28 indicated that a protective association between rs4663396 and Crohn's disease has also been confirmed in Germany.…”
Section: Discussionmentioning
confidence: 89%
“…Some of these antibodies were specifically associated with CD diagnosis and complications in several studies [ 13 , 14 , 36 ]. Antiglycan serologic responses in Indian patients with CD [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and non-Indian Asian cohorts [ 38 , 39 ] were scarcely reported. Interestingly, despite a comparable overall rate of seropositivity, differences between the cohorts were noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Quality and quantity were tested using a NanoDrop One spectrophotometer (Thermo Scientific, Waltham, MA, USA). To explore possible genetic biomarkers, we genotyped 20 CD-associated single-nucleotide polymorphisms (SNPs) that were reported in either Western ( n = 13) or Indian ( n = 7) cohorts in association with CD diagnosis [ 19 , 20 , 21 ] and course [ 22 , 23 ] (listed in Supplementary Table S1 ). These included polymorphisms in protein binding domain 2 ( NOD2 ) [ 24 ] and the genes regulating the autophagic response to invading pathogens (autophagy pathway-related 16 like 1 ( ATG16L1 ) and immunity-related GTPase 1 ( IRGM )) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%